Atmospheric neutrino results from IceCube-DeepCore and plans for PINGU - Jason Koskinen, D; IceCube-Gen2 Collaboration (Institute of Physics, 2017)
The IceCube neutrino observatory at the South Pole is the largest operating neutrino detector in the world and spans a wide range of science topics, from astronomy at the PeV-scale to particle physics at the GeV-scale. We present results from the search for a light, O(1) eV 2 , sterile neutrino using the large IceCube array and, separately, using the lower energy extension DeepCore sub-array. Additionally, we review the atmospheric neutrino results and expected sensitivities related to oscillation physics (ν μ disappearance and ν τ appearance) as well as new limits on non-standard interactions. Continuing the success of the IceCube-DeepCore physics program, a proposed next generation in-fill detector with increased sensitivity to neutrinos of O(1) GeV will be covered.